Analytical pyrolysis for determining the molecular composition of contemporary monosulfidic black ooze. - Lockhart, Robert; Berwick, Lyndon; Greenwood, Paul; Grice, Kliti; Kraal, P.; Bush, R. (Elsevier, 2013)
On-line flash pyrolysis, micro-scale sealed vessel (MSSV) pyrolysis and catalytic hydropyrolysis (HyPy) were used to characterise the insoluble, macromolecular organic component of monosulfidic black oozes (MBO) which have accumulated within the contemporary eutrophic environment of the Peel–Harvey estuary system (Geographe Bay, Western Australia). Pyrolysates were analysed by gas chromatography–mass spectrometry (GC–MS) and the relative characterisation potential of the three pyrolysis techniques were evaluated with a particular interest in their sensitivity to organic sulfur compounds (OSCs). A similarity of results obtained from three different parts of the ∼1 m cores sampled suggests a largely homogenous organic composition throughout the unit. The different pyrolysis techniques did, however, show several notable product differences, particularly the gaseous products detected by the on-line methods of flash- and MSSV-pyrolysis.The very high (i.e., ballistic) heating rate of flash-Py produced very high proportions of gaseous products (e.g., CO2, H2S and SO2). A strong terrestrially sourced product component was reflected in all three pyrolysates profiles: flash-Py showed relatively high concentrations of lignocellulose products, while MSSV-Py and HyPy produced an abundance of plant wax (>n-C20) n-alkanes. Additionally, quantitatively significant levels (7–14% of total GC product signal) of several higher plant derived terpenoids (e.g., cadalene, p-cymene and calamanene) were identified by MSSV-Py. MSSV-Py also produced far greater overall concentrations of GC-amenable products than flash-Py, including a 14-fold increase of OSCs, which comprised nearly 10% of the total sulfur signal (i.e., organic plus ‘inorganic’ sulfur; cf. 4% of flash pyrolysis). An extended series of alkyl (<C9) substituted thiophenes were the main OSCs. HyPy, in contrast, showed no evidence of OSCs – confirmed by GC-flame photometric detection (FPD). HyPy is renowned for its capacity to preserve primary structural units, so its failure to detect thiophenes and other OSCs abundant in the corresponding analysis, suggests these are not indigenous to the macromolecular fraction of the MBO. The detection of these products by MSSV-Py, and to a lesser extent flash-Py, suggests these pyrolysis methods initiate a restructuring of sulfur species towards more thermally stable secondary configurations. One explanation for the limited diagnostic S-speciation data obtained from the present analysis may be the existence of most of the S in the MBO as bridging units between covalently bound organic structures. These relatively weakly bound associations may form on the reaction of reduced sulfur species (from bacterial sulfate reduction) with highly functionalised organic compounds during the early stages of diagenesis.